Pain-related disability, PTSD symptoms, and mood among a comorbid chronic pain and PTSD sample prior to and during the COVID-19 pandemic. (May 2022) - Reed, David E; Cobos, Briana; Lehinger, Elizabeth A; Nabity, Paul S; Vail, Kenneth E; McGeary, Donald D
There is a knowledge gap when treating comorbid chronic pain and posttraumatic stress disorder (PTSD) during the COVID-19 pandemic. Addressing this gap, 169 individuals (57.4% female), aged 39.8 years were recruited based on levels of pain-related disability and PTSD symptoms. Participants were assessed prior to, and during, the COVID-19 pandemic. Improvements in pain-related disability were marginally attenuated for the comorbid group, compared to the chronic pain group. Results show that some condition-specific symptoms may not have been affected by the COVID-19 pandemic. Cautious interpretation is warranted due to only two time points and the lack of a diverse sample.